A girl walks home alone at night - Amirpour, Ana Lily; Vand, Sheila; Marandi, Arash; Marnò, Mozhan, 1980-; Rains, Dominic, 1982-; Eghbali, Milad; Shadanloo, Rome; Safai, Reza Sixo
In the Iranian ghost-town Bad City, a place that reeks of death and loneliness, the townspeople are unaware they are being stalked by a lonesome vampire.